For a Healthy (and) Higher Education: Evidences from Learning Outcomes in Health Sciences - Ângela Leite; Diana Soares; Hélder Fernando Pedrosa e Sousa; Diogo Guedes Vidal; Maria Alzira Pimenta Dinis; Diana Dias (MDPI AG, 2020)
Increased recognition of outcomes, or competency-based education, has evolved across higher education on health sciences. However, there is significant diversity in the current study of Portuguese programmes. Considering learning outcomes (LO) as indicators of knowledge, skills, abilities, attitudes and the understanding that the student will gain as a result of an educational experience, this study aims to explore which LO are emphasised on the study programmes of health sciences in Portugal. Through a qualitative methodology, carried out through MAXQDA software, all LO of all Portuguese health sciences study programmes submitted to quality accreditation to the Portuguese Agency for Assessment and Accreditation of Higher Education (A3ES) since 2009 until 2016 were analysed. Although specific knowledge was the most referenced LO, transversal skills were also emphasized, such as critical and reflexive analysis/critical thinking, research, ability to organize and plan and professional ethics. Significant differences were found between LO selection when the analysis was made by comparing the diverse study programmes. This required assortment of knowledge and skills seems to reflect not only the specificities of each health science programme but also the challenging demands on professionals in the 21st century, along with the necessary changes imposed by society, fostering intercultural understanding, tolerance, mutual respect and an ethic of global citizenship and shared responsibility, crucial enablers of educational development for all in the scope of the 2030 Agenda for Sustainable Development.